Busana Pesta dan Kasual Terinspirasi dari Buah Sawit - Aini, Nur; Kencana, Mega; Yanuarmi, Dini (Style : Journal of Fashion Design, 2024)
The work report entitled "Party and Casual Clothing Inspired by Palm Fruit Colors" is in the form of party and casual clothing. This work is sourced from the colors found in palm fruit and combined with palm oil batik motifs. The creation of clothing with a combination of palm-oil batik motifs and unique creativity aims to introduce to the public that anything around us can be a source of ideas for making clothing designs. The shape and color of the palm fruit are unique, featuring color gradations such as yellow, tiger, cherry, crimson, and wine. In creating this work, the craftsman went through three stages: the exploration stage, which involved seeking information about palm oil in West Pasaman; the design stage, which included viewing reference images, compiling the creation concept, mood boards, and making designs; and the embodiment stage, which involved cutting patterns, sewing, and finally presenting the clothing in a fashion show. The works produced include party and casual clothing, namely ready-to-wear clothing 1, ready-to-wear clothing 2, ready-to-wear clothing 3, ready-to-wear deluxe 1 clothing, ready-to-wear deluxe 2 clothing, and haute couture.